Immunomodulation and Immune Escape Strategies of Gastrointestinal Helminths and Schistosomes - Wiedemann, Marie; Voehringer, David (Frontiers in Immunology, 2020)
Parasitic worms (helminths) developed various immunoregulatory mechanisms to counteract the immune system of their host. The increasing identification and characterization of helminth-derived factors with strong immune modulatory activity provides novel insights into immune escape strategies of helminths. Such factors might be good targets to enhance anti-helminthic immune responses. In addition, immunosuppressive helminth-derived factors could be useful to develop new therapeutic strategies for treatment of chronic inflammatory conditions. This review will take an in depth look at the effects of immunomodulatory molecules produced by different helminths with a focus on schistosomes and mouse models of hookworm infections.